Help with proving Biconditional equivalence

  • Thread starter the baby boy
  • Start date
  • Tags
    Equivalence
In summary, the proof for (P→Q) ∧ (Q→R) = (P→R) ∧ [(P↔Q) ∨ (Q↔R)] can be done by expanding the left side and using distributivity to reduce it to the right side. From there, you can then use the distributive law again to put it into disjunctive normal form. Alternatively, you can also use a truth table to prove the equivalence.
  • #1
the baby boy
7
0
show that P [itex]\leftrightarrow[/itex] Q is equal to (P[itex]\wedge[/itex]Q) [itex]\vee[/itex] ([itex]\neg[/itex]P [itex]\wedge[/itex][itex]\neg[/itex]Q)

(P→Q) [itex]\wedge[/itex] (Q→P)
([itex]\neg[/itex]P[itex]\vee[/itex]Q) [itex]\wedge[/itex] ([itex]\neg[/itex]Q[itex]\vee[/itex]P)

[[itex]\neg[/itex](P[itex]\wedge[/itex][itex]\neg[/itex]Q)[itex]\wedge[/itex][itex]\neg[/itex](Q[itex]\wedge[/itex][itex]\neg[/itex]P)]

[itex]\neg[/itex][(P[itex]\wedge[/itex][itex]\neg[/itex]Q)[itex]\vee[/itex](Q[itex]\wedge[/itex][itex]\neg[/itex]P)]

I don't know which law to use from this point on to prove the equivalence.
 
Physics news on Phys.org
  • #2
You started right with going from (P→Q) ∧ (Q→P) to (¬P∨Q) ∧ (¬Q∨P), but from there on you are taking the wrong path. Not invalid; just wrong. That path won't get you to the desired result. Try using distributivity.

Or just use the dumb approach of showing that P ↔ Q and (P∧Q) ∨ (¬P ∧¬Q) have the identical truth tables.
 
  • #3
How can I use the distributive law here? I mean, I don't see a common letter with a connective to factor out.
 
  • #4
Why not just do a truth table?
 
  • #5
the baby boy said:
How can I use the distributive law here? I mean, I don't see a common letter with a connective to factor out.
Who said you need a common letter to factor out? All you need is a common item.

Given a conjunctive normal form (A∨B)∧(C∨D), you can use either (A∨B) or (C∨D) as the common item in applying distributivity. Using (A∨B) as the common item yields ((A∨B)∧C)∨((A∨B)∧D) . (You'll get (A∧(C∨D))∨(B∧(C∨D)) if you use (C∨D) as the common item.) Now apply the distributive law again to put this into disjunctive normal form.
Bacle2 said:
Why not just do a truth table?
Perhaps because the instructor said something along the lines of "You can easily prove these conjectures by showing they have the same truth tables. Do that and you will receive zero points on this homework."
 
  • #6
distributing (¬P∨Q) over (¬Q∨P) we get:

(¬P∨Q)∧(¬Q∨P) = [(¬P∨Q)∧¬Q]∨[(¬P∨Q)∧P]

can you see how to continue?
 
  • #7
Hello,

Thank you all for helping me with this. I am only self-learning basic logic from a book, and the author never worked out distribution of all of the content in the parentheses to another, so I only thought you could distribute one letter at a time.

I have a new problem:

Prove (P [itex]\rightarrow[/itex]Q) [itex]\wedge[/itex] (Q [itex]\rightarrow[/itex] R) = (P [itex]\rightarrow[/itex] R) [itex]\wedge[/itex] [(P [itex]\leftrightarrow[/itex] Q) [itex]\vee[/itex] (Q [itex]\leftrightarrow[/itex] R)]

I was able to get this far:
([itex]\neg[/itex]P [itex]\wedge[/itex] [itex]\neg[/itex]Q) [itex]\vee[/itex] [([itex]\neg[/itex]P [itex]\vee[/itex] Q) [itex]\wedge[/itex] R] = ([itex]\neg[/itex]P [itex]\vee[/itex] R) [itex]\wedge[/itex] [(([itex]\neg[/itex]P [itex]\wedge[/itex] [itex]\neg[/itex]Q) [itex]\vee[/itex] (P [itex]\wedge[/itex] Q)) [itex]\vee[/itex] (([itex]\neg[/itex]R [itex]\wedge[/itex] [itex]\neg[/itex]Q) [itex]\vee[/itex] (R [itex]\wedge[/itex] Q))]

How should I proceed? Should I continue to expand the left side of the equation or somehow try to reduce the right?
 

1. What is Biconditional equivalence?

Biconditional equivalence is a logical statement that indicates that two statements are equivalent. This means that if one statement is true, the other statement must also be true, and if one statement is false, the other statement must also be false.

2. How is Biconditional equivalence represented in symbols?

Biconditional equivalence is typically represented by the symbol "↔" or "iff" (if and only if). For example, the statement "p if and only if q" can be represented as "p ↔ q" or "p iff q".

3. What is the difference between Biconditional equivalence and other logical statements?

Biconditional equivalence is different from other logical statements (such as conditional statements or conjunctions) because it requires both statements to be true or both statements to be false for the overall statement to be true. In other words, both statements must have the same truth value in order for the biconditional statement to be true.

4. How can I prove Biconditional equivalence?

To prove Biconditional equivalence, you can use a truth table or logical equivalences. A truth table is a table that shows all possible combinations of truth values for the component statements and the resulting truth value of the biconditional statement. Logical equivalences are a set of rules that can be used to manipulate logical statements in order to show their equivalence.

5. What is the importance of understanding Biconditional equivalence?

Understanding Biconditional equivalence is important in many fields of science, as it allows us to make logical deductions and draw conclusions based on the relationships between two statements. It is also a fundamental concept in mathematics and computer science, as it is used in mathematical proofs and logical operations.

Similar threads

  • Set Theory, Logic, Probability, Statistics
Replies
2
Views
1K
  • Set Theory, Logic, Probability, Statistics
Replies
2
Views
5K
Replies
10
Views
2K
  • Set Theory, Logic, Probability, Statistics
Replies
6
Views
2K
  • Set Theory, Logic, Probability, Statistics
Replies
3
Views
1K
  • Engineering and Comp Sci Homework Help
Replies
1
Views
1K
  • Set Theory, Logic, Probability, Statistics
Replies
2
Views
1K
  • Set Theory, Logic, Probability, Statistics
Replies
2
Views
1K
Replies
0
Views
450
  • Set Theory, Logic, Probability, Statistics
Replies
1
Views
3K
Back
Top